2011
DOI: 10.1039/c1cp21190k
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular OH⋯π interactions in alkenols and alkynols

Abstract: The vibrational overtone spectra of propargyl alcohol (prop-2-yn-1-ol, PA), allyl alcohol (prop-2-en-1-ol, AA), propargyl carbinol (but-3-yn-1-ol, PC) and allyl carbinol (but-3-en-1-ol, AC) were recorded with intracavity laser photoacoustic spectroscopy (ICL-PAS) in the Δv(OH) = 3, 4 and 5 regions for propargyl alcohol and allyl alcohol and in the Δv(OH) = 4 and 5 regions for propargyl carbinol and allyl carbinol. Local mode anharmonic oscillator calculations were performed with explicitly correlated coupled c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 80 publications
2
47
0
2
Order By: Relevance
“…The microwave spectrum of PA has confirmed the occurrence of only the g-PA [6,7]. Similarly, for propargyl thiol (C 3 H 4 S) [12][13][14][15] and propargyl selenol (C 3 H 4 Se) [16], only the g-PA conformer has been observed.…”
Section: H 3 þC 3 H 3 /C 6 H 6 /Pah/sootsupporting
confidence: 61%
See 1 more Smart Citation
“…The microwave spectrum of PA has confirmed the occurrence of only the g-PA [6,7]. Similarly, for propargyl thiol (C 3 H 4 S) [12][13][14][15] and propargyl selenol (C 3 H 4 Se) [16], only the g-PA conformer has been observed.…”
Section: H 3 þC 3 H 3 /C 6 H 6 /Pah/sootsupporting
confidence: 61%
“…Calculations at the CCSD(T)-F12/VDZ-F12 level of theory [7] indicated the g-PA to be the lower energy conformer, with the higher energy trans structure (t-PA) being about 6.7 kJ/mol above g-PA. Hirota proposed that the intramolecular hydrogen bond between the eOH group and p electrons, was the reason for the g-PA being the ground state conformer [8]. Subsequent atoms-in-molecules (AIMs) investigations did not support this explanation [9], as it was shown that there did not exist any bond critical point between the two functional groups mentioned above.…”
Section: H 3 þC 3 H 3 /C 6 H 6 /Pah/sootmentioning
confidence: 99%
“…38 Figure 2a reports the mass-resolved 1cR2PI excitation spectrum of bare p-ClE S in the 0 0 0 origin region, obtained by monitoring the parent ion signal at m/z = 156. The 1cR2PI excitation spectrum of the 37 Cl isotopomer is not reported here as it is nearly identical to the The Journal of Physical Chemistry A Article corresponding 35 Cl ones, with the vibrational frequencies differing by no more than 1 cm −1 .…”
Section: Resultsmentioning
confidence: 79%
“…In particular, intermolecular hydrogen bonds are characterised by the existence of a critical point for which the gradient of the electron density becomes zero [190]. The recently developed NCI methods extends this definition to zones of very low gradient and density, making it applicable to intramolecular hydrogen bonds for which repulsion competes with the formation of the hydrogen bond [191]. A whole description of the method can be found in the seminal article [192] and its application to inter vs. intramolecular hydrogen bonding including chiral systems has been recently reported [193].…”
Section: Visualisation Of the Ncismentioning
confidence: 99%